A Multiscale and Multimethod Approach to Assess and Mitigate Concrete Damage Due to Alkali–Silica Reaction. Issue 6 (24th May 2022) - Weise, Frank; von Werder, Julia; Manninger, Tanja; Maier, Bärbel; Fladt, Matthias; Simon, Sebastian; Gardei, André; Hoehnel, Desirée; Pirskawetz, Stephan; Meng, Birgit
Abstract : Alkali–silica reaction (ASR) is a chemical reaction within concrete which can lead over time to cracking and spalling. Due to the complexity of the problem, it still causes damage to concrete constructions worldwide. The study aims to illustrate the interdisciplinary research of the German Federal Institute for Materials Research and Testing (BAM) within the last 20 years, considering all aspects of ASR topics from the macro‐ to the micro‐level. First, methods for characterization and assessment of ASR risks and reaction products used at BAM are explained and classified in the international context. Subsequently, the added value of the research approach by combining different, preferably nondestructive, methods across all scales is explained using specific examples from a variety of research projects. Aspects covered range from the development of new test setups to assess aggregate reactivity, to analysis of microstructure and reaction products using microscopical, spectroscopical, and X‐ray methods, to the development of a testing methodology for existing concrete pavements including in‐depth analysis of the visual damage indicator and the deicing salt input using innovative testing techniques. Finally, research regarding a novel avoidance strategy that makes use of internal hydrophobization of the concrete mix is presented. Abstract : Alkali–silica reaction still causes damage to concrete constructions worldwide. The study illustrates the interdisciplinary research of the German Federal Institute for Materials Research and Testing. The added value of combining different, preferably nondestructive, methods across all scales is explained using examples from a variety of research projects. Furthermore, a novel avoidance strategy is presented.